Taxonomic and morphological studies on the Lygephila dorsigera (Walker, 1865) species-group, with description of a new species (Lepidoptera, Erebidae, Toxocampinae) - Pekarsky, Oleg (Zootaxa, 2016)
A new species of the L. dorsigera species-group, Lygephila pallidivena sp. n. is described. A diagnostic comparison is made with L. dorsigera and Lygephila lilacina (Butler, 1878). The female genitalia of the holotype of L. dorsigera is described and illustrated for the first time, and Lygephila kishidai Kinoshita, 1989 is treated here as a junior subjective synonym, syn. n.